Characterization of pax1, pax9, and uncx sclerotomal genes during Xenopus laevis embryogenesis - Sanchez, Romel Sebastian (2013)
Background: The axial skeleton develops from the sclerotome, a mesenchymal cell population derived from somites. Sclerotomal cells migrate from somites to the perinotochordal and perineural space where they differentiate into chondrocytes to form cartilage and bone. In anurans, little is known about the way how the sclerotome changes as development proceeds and how these events are regulated at the molecular level. Pax1, Pax9, and Uncx4.1 genes play a central role in the morphogenesis of the axial skeleton in vertebrates, regulating cell proliferation and chondrogenic specification of the sclerotome. Results: In this work, we cloned and examined through whole-mount in situ hybridization and reverse transcriptasepolymerase chain reaction the expression patterns of pax1, pax9, and uncx transcription factors in the anuran Xenopus laevis. Conclusions: We found that these genes are similarly expressed in the sclerotome and in the pharyngeal pouch. A detailed analysis of the location of these transcripts showed that they are expressed in different subdomains of the sclerotomal compartment and differ from that observed in other vertebrates.